Model financial resources enterprise to adapt to dynamic market conditions environment - Maliukov, Volodymyr; Marynenko, Natalia (Skhid, 2016)
In the article the mathematical model of financial management of enterprises to adapt for dynamic market environment conditions. Practical implementation proposed model will choose the specific financial management solutions (share of financial resources for adaptation) and see how important financial resources to the parties the next time. This makes it possible to get the desired result for the company, the interaction of the company with the counterparty. Proved that the management of the enterprise is useful in their practical work tools that allow finding optimal behavior strategies of interaction, which in turn makes it possible to assess the effectiveness of response on a dynamic environment on the basis of risk. The model which proposed clearly shows interrelations in business finance and banking structures, but some things are also specific industries.